2020
DOI: 10.1038/s41380-020-00973-3
|View full text |Cite
|
Sign up to set email alerts
|

The genie in the bottle-magnified calcium signaling in dorsolateral prefrontal cortex

Abstract: Neurons in the association cortices are particularly vulnerable in cognitive disorders such as schizophrenia and Alzheimer’s disease, while those in primary visual cortex remain relatively resilient. This review proposes that the special molecular mechanisms needed for higher cognitive operations confer vulnerability to dysfunction, atrophy, and neurodegeneration when regulation is lost due to genetic and/or environmental insults. Accumulating data suggest that higher cortical circuits rely on magnified levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 189 publications
(262 reference statements)
0
92
0
Order By: Relevance
“…In contrast to the dlPFC, high levels of catecholamines and glucocorticoids enhance the affective functioning of the amygdala (81)(82)(83), thus flipping the brain from a reflective to reflexive state. The rapid loss of dlPFC executive and working memory functions from a hypercatecholaminergic state has now been documented in humans (84)(85)(86) in addition to the original studies in rodents and monkeys (9,77,78). Thus, BA25 and amygdala can rapidly remove their regulation from higher order PFC circuits through activation of excessive catecholamine release in these higher PFC regions (Figure 4B).…”
Section: Figure 4 | (A)mentioning
confidence: 88%
See 3 more Smart Citations
“…In contrast to the dlPFC, high levels of catecholamines and glucocorticoids enhance the affective functioning of the amygdala (81)(82)(83), thus flipping the brain from a reflective to reflexive state. The rapid loss of dlPFC executive and working memory functions from a hypercatecholaminergic state has now been documented in humans (84)(85)(86) in addition to the original studies in rodents and monkeys (9,77,78). Thus, BA25 and amygdala can rapidly remove their regulation from higher order PFC circuits through activation of excessive catecholamine release in these higher PFC regions (Figure 4B).…”
Section: Figure 4 | (A)mentioning
confidence: 88%
“…(B) The increasing timescales across the primate cortical hierarchy, and their relationship to GRIN2B expression. Based on (11) and (9). LIP, lateral intraparietal cortex; MT, middle temporal visual cortex.…”
Section: Primate Prefrontal Cortical Circuitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several task-based fMRI studies have suggested that normalization of hypoactivity in the dorsal prefrontal cortex may be a marker of antipsychotic efficacy 69 , consistent with results of cross-sectional studies comparing treatment-resistant to treatment-responsive patients with schizophrenia 70 . A mechanistic understanding of dorsal prefrontal cortex suggests that tight regulation of calcium-cAMP signaling is required for optimal function, and that several pharmacologic approaches may be tested that can ameliorate calcium dysregulation 71 . Intriguingly, emerging evidence suggests that non-pharmacologic approaches to schizophrenia treatment such as repetitive transcranial magnetic stimulation (rTMS) and cognitive remediation therapy may also effectively modulate activity and connectivity in the dorsal prefrontal cortex 72 .…”
Section: Discussionmentioning
confidence: 99%